Selective Flotation of Copper Oxide Minerals with A Novel Amino-Triazole-Thione Surfactant: A Comparison to Hydroxamic Acid Collector. (3rd March 2020) - Liu, Jun; Hu, Zhe; Liu, Guangyi; Huang, Yaoguo; Zhang, Zhiyong
ABSTRACT: Developing specific flotation collectors to improve the separation and enrichment of copper oxide minerals from their ores is still a challenging job. In this article, a novel chelating collector, 5-(2, 4, 4-trimethylpentyl)-4-amino-1, 2, 4-triazolidine-3-thione (TMATT), was designed to separate and recover copper oxide minerals, and its flotation response to malachite, calcite, and quartz was compared with that of the traditional collector n-octyl hydroxamic acid (OHA). The findings of contact angle and micro-flotation indicated that TMATT exhibited stronger hydrophobization and better flotation performances to malachite than OHA, and also held the high flotation selectivity against quartz and calcite. The bench-scale flotation outcomes showed that TMATT achieved the high-efficient flotation separation and enrichment of copper oxide minerals from the mixed sulfide-oxide copper ore. XPS, FTIR, AFM, and zeta potential deduced that the adsorption of malachite toward TMATT was related to the reduction of surface Cu(Ⅱ) to Cu(Ⅰ) and the formation of TMATT-Cu(Ⅰ) surface complexes in which the exocyclic N and S atoms of TMATT bonded with the surface Cu(Ⅰ) on malachite. The superior hydrophobicity of TMATT-Cu(I) surface complexes in comparison to that of OHA-Cu(Ⅱ) surface complexes, the favorable five-membered ring bonding mode on malachite surfaces and the preferable chelating selectivity to soft acid Cu(Ⅰ) rather than to hard acid Ca(Ⅱ), deserved TMATT to possess better flotation response to malachite against calcite than OHA.